Gaudium et Spes: an enormous step towards overcoming the dualism between natural marriage and the Sacrament of Matrimony = Gaudium et Spes : un grand pas visant à surmonter le dualisme entre le mariage naturel et le sacrement de mariage = Gaudium et Spes : il passo miliare nel vincere il dualismo tra il matrimonio naturale e il sacramento del matrimonio - Pastwa, Andrzej (Philosophy & canon law, 2016)
In this study the author undertakes an attempt of an integral interpretation of theVaticanum II magisterium on the sacrament of matrimony. At the beginning he formulates ahypothesis which implies that next to the assumptions of an adequate anthropology and methodological remarks, which were made, lies an idea that “gives order” to the appropriate discourse in the area of matrimonium christifidelium. It is about the significant thesis which suggests that the “unity,” paradigm of the contemporary ecclesiology, constitutes an inseparable hermeneutical key to the understanding of Christian matrimony. The concentration in the old code (CIC 1917) of regulations concerning sacramentum matrimonii, on the constitutive moment of entering into marriage (matrimonium in fieri), carried many implications of a theological and legal nature. The matter of this sacrament was defined as (mutual) giving of the right to the body to the other person, whereas the form as the acceptance of this right. In turn, the legalistic depiction of the sacramentality of matrimony and binding it with the condition of a rightfully received baptism, regardless of the presence or absence of faith, in practice by no means meant that baptism is to constitute a foundation of building a sacramental reality of matrimony. Such automatism — a result of a substantial and juridical approach—by misrepresenting, in a significant way, the personal core of the event of the sacrament, brought this sacrament closer to magic. This is where the significance of Council Fathers’ work, aimed at overcoming the dualism between natural marriage and the sacrament of matrimony, stems from. The person who significantly contributed to the presentations of Christian matrimony, as closely connected with the secret of Christ, was a prominent theologian of law Eugenio Corecco. One of the rhetorical questions—that constitutes the structure of the fundamental part of the study—is as follows: Is it not desirable(or even essential) to interpret the most crucial code regulations of matrimonial law accordingto a proper “anthropological key,” that is, through the prism of the Mystery of Incarnation—in relation to an internal dynamics of followers’ (nupturients’) affiliation to communioEcclesiae?